Kontrol Infant Warmer Dilengkapi Baterai Dan Inverter - Muhammad Dwi Mubarok; Mohamad Sofie; Mohammad Rofii’i (LPPM POLBITRADA, 2025)
A common problem that occurs in newborn babies is difficulty in adjusting body temperature to the surrounding environment. The baby's body temperature while in the womb ranges from 34°C to 37°C. When born, babies are susceptible to experiencing a decrease in body temperature which can cause hypothermia. Hypothermia is one of the main causes of death in newborns. Infant Warmer is a medical device specifically designed to provide a stable body temperature to newborns or premature babies. The main purpose of using an infant warmer is to prevent hypothermia, which is a condition of body temperature that is too low, which can cause serious health problems in babies. The PID (Proportional, Integral, Derivative) controller is a combination of Proportional, Integral, Derivative controllers that cover each other. . By using all three as Proprtional, Integral, Derivative control elements, each as a whole aims to accelerate the system reaction, use offsets and produce large initial changes. The PID controller calculates the error as the difference between the measured process variable and the desired set point. After designing the software using Arduino and having designed the hardware, a function test and data collection were carried out on the tool that will be discussed in this chapter which aims to prove the truth of the results of the circuit design and testing the function of the tool obtained by the author from the data taken from the specified measurement point, then it will be analyzed to determine how big the error rate is which will be expressed in percent (%).